Perancangan Sistem Informasi Evaluasi Program Bantuan Sosial Di Dinas Sosial Pemberdayaan Perempuan Dan Perlindungaan Anak Kabupaten Batu Bara (Jurnal Sistem Informasi dan Ilmu Komputer, 2025)
The development of information technology has had a significant impact in various sectors, including in the management of social assistance programs. At the Social Service for Women's Empowerment and Child Protection of Batu Bara Regency, the evaluation process for the implementation of social assistance programs is still carried out manually, which causes delays in data collection, analysis, and report preparation. Therefore, an information system is needed that can help speed up and facilitate the evaluation of the program. This study aims to design a Social Assistance Program Evaluation Information System that can integrate data on aid recipients, types of assistance, recipient status, and program effectiveness evaluation. This system is designed using the Waterfall method which consists of the stages of needs analysis, design, implementation, testing, and maintenance. The platform used in the development of this system is web-based to facilitate access from various devices. The results of this study show that the design of an integrated information system can increase efficiency in collecting evaluation data and speed up the reporting process to related parties. In addition, this system is expected to increase transparency and accountability in the implementation of social assistance programs, so that the impact of the program can be more measurable and on target.